(3aj eSGFd GdQVGYs - (3GdfLaj, , GdCYSe, eMeO Hf Ydj Hf MSjf Hf eMeO ` J (B1233 (3g`s
(3ChdgG (B:s
(3GdMeO ddg (B.. (3hHYO aGYde HCf GdOGYj ddfXe aj eSGFd GdQVGY (B** (3Cfj QCjJgG cKjQI GdTYH hGdHMK Yf CMcGegG eeG hLH (B...s
(3BNQgG (B:s
.. (3dcf CJi ajgG MOjKG Cf ef CMdgG Gdehdi abO WGH GddHf (B** (3Ke dfUd HYO PGdebGd Ydi GdfHj GdeUWai hBd (B...s
(3aj HWGbI cGTa GdZWGA (B: (3GdfGSN (B: (3YHj Hf eMeO QVG cGTa GdZWGAs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B6\297s
(3GdPQjYI (B1\2367s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3abg GdePGgH GdCNQis